2021
DOI: 10.3390/ijerph18084324
|View full text |Cite
|
Sign up to set email alerts
|

Second-Hand Smoke and Its Synergistic Effect with a Body-Mass Index of >24.9 kg/m2 Increase the Risk of Gout Arthritis in Indonesia

Abstract: To analyze the association between smoking status (active smoking and exposure to Second-Hand Smoking (SHS)) and the synergistic effect of smoking status and BMI with gout risk, a community-based case-control design was undertaken among 385 participants, including 304 healthy controls and 81 gout patients from seven community health services. Adjusted Odd Ratios (AORs) and 95% Confidence Interval (CIs) of gout for active smoking and SHS were 3.26 (95% CI = 1.07~9.90) and 4.67 (95% CI = 2.18~10.00) compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 63 publications
(107 reference statements)
0
18
0
Order By: Relevance
“…Currently, intermittent drug use for pain relief contributes to renal impairment risk that is attributed to under-excretion of urate and is a cause of death in gout patients (Kurniasari et al, 2021; Padang et al, 2006). This indicates that further research is required on gout pain management such as non-pharmacological or adjunct interventions (Abhishek & Doherty, 2018).…”
Section: Pain Relief For Goutmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, intermittent drug use for pain relief contributes to renal impairment risk that is attributed to under-excretion of urate and is a cause of death in gout patients (Kurniasari et al, 2021; Padang et al, 2006). This indicates that further research is required on gout pain management such as non-pharmacological or adjunct interventions (Abhishek & Doherty, 2018).…”
Section: Pain Relief For Goutmentioning
confidence: 99%
“…In a global ethnic group comparison, Malayo-Polynesian males had higher rates of gout and hyperuricemia than Caucasian men (Darmawan, 1992; Dyah Kurniasari et al, 2021). Another study also reported that gout is a common arthritic illness in Malayo-Polynesian people (Kurniasari et al, 2021; Padang et al, 2006), and Indonesians are included in the Malayo-Polynesian ethnic group (Klamer, 2019). These data indicate that gout disease is a significant public health problem in Indonesia after considering genetic factors and their interplay with environmental factors (Darmawan, 1992).…”
mentioning
confidence: 99%
See 3 more Smart Citations